Characterization of am404, an amber mutation in the simian virus 40 T antigen gene. - Rawlins, D R (1983)
We analyzed the biological activity of an amber mutation, am404, at map position 0.27 in the T antigen gene of simian virus 40. Immunoprecipitation of extracts from am404-infected cells demonstrated the presence of an amber protein fragment (am T antigen) of the expected molecular weight (67,000). Differential immunoprecipitation with monoclonal antibody demonstrated that am T antigen was missing the carboxy-terminal antigenic determinants. The amber mutant was shown to be defective for most of the functions associated with wild-type T antigen. The mutant did not replicate autonomously, but this defect could be complemented by a helper virus (D. R. Rawlins and N. Muzyczka, J. Virol. 36:611-616, 1980). The mutant failed to transform nonpermissive rodent cells and did not relieve the host range restriction of adenovirus 2 in monkey cells. However, stimulation of host cell DNA, whose functional region domain has been mapped within that portion of the protein synthesized by the mutant, could be demonstrated in am404-infected cells. A number of unexpected observations were made. First, the am T antigen was produced in unusually large amounts in a simian virus 40-transformed monkey cell line (COS-1), but overproduction was not seen in nontransformed monkey cells regardless of whether or not a helper virus was present. This feature of the mutant was presumably the result of the inability of am T antigen to autoregulate, the level of wild-type T antigen in COS-1 cells, and the unusually short half-life of am T antigen in vivo. Pulse-chase experiments indicated that am T antigen had an intracellular half-life of approximately 10 min. In addition, although the am T antigen retained the major phosphorylation site found in simian virus 40 T antigen, it was not phosphorylated. Thus, phosphorylation of simian virus 40 T antigen is not required for the stimulation of host cell DNA synthesis. Finally, fusion of am404-infected monkey cells with Escherichia coli protoplasts containing appropriate procaryotic suppressor tRNAs showed that am404 is a suppressible nonsense mutation.